2019
DOI: 10.1136/gutjnl-2018-318059
|View full text |Cite
|
Sign up to set email alerts
|

KrasandLkb1mutations synergistically induce intraductal papillary mucinous neoplasm derived from pancreatic duct cells

Abstract: ObjectivePancreatic cancer can arise from precursor lesions called intraductal papillary mucinous neoplasms (IPMN), which are characterised by cysts containing papillae and mucus-producing cells. The high frequency of KRAS mutations in IPMN and histological analyses suggest that oncogenic KRAS drives IPMN development from pancreatic duct cells. However, induction of Kras mutation in ductal cells is not sufficient to generate IPMN, and formal proof of a ductal origin of IPMN is still missing. Here we explore wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Interestingly, in most models with duct cell-specific expression of oncogenic Kras, the resulting neoplasia either resembled IPMNs or otherwise bypassed low-grade PanINs. [31][32][33]36 This suggests that in some genetic contexts, the pattern of neoplastic progression differs, based on the cell type in which oncogenic Kras is expressed.…”
Section: The Pancreatic Ductal Adenocarcinoma Cell Of Originmentioning
confidence: 99%
“…Interestingly, in most models with duct cell-specific expression of oncogenic Kras, the resulting neoplasia either resembled IPMNs or otherwise bypassed low-grade PanINs. [31][32][33]36 This suggests that in some genetic contexts, the pattern of neoplastic progression differs, based on the cell type in which oncogenic Kras is expressed.…”
Section: The Pancreatic Ductal Adenocarcinoma Cell Of Originmentioning
confidence: 99%
“…The massive replacement of the pancreas by cysts in KPN +/− mice is of relevance given the increasing diagnosis of pancreatic cysts, providing a new mouse model for these lesions. Other GEMMs recently used to study pancreatic cysts/IPMNs are based on the activation of mutant GNAS and KRAS in pancreatic progenitors, leading to IPMN and PDAC [5] or the deletion of LKB1 [57,58], PTEN (with or without mutant KRAS ) [59], BRG1 [55], or FBW7 [15] in ductal cells. Whether cystic lesions from KPN +/− mice show deregulated PTEN, LKB1 or BRG1 expression, or acquire GNAS mutations, remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…I Cobo et al leading to IPMN and PDAC [5] or the deletion of LKB1 [57,58], PTEN (with or without mutant KRAS) [59], BRG1 [55], or FBW7 [15] in ductal cells. Whether cystic lesions from KPN +/− mice show deregulated PTEN, LKB1 or BRG1 expression, or acquire GNAS mutations, remains to be elucidated.…”
mentioning
confidence: 99%
“…The role of KRAS in PDAC and other human cancers is well established [69]; mutations in this gene are an early event during IPMN development and are present in up to 80% of the cases [5,[70][71][72]. A recent study confirmed the synergistic action of KRAS and tumor suppressor gene mutations for development of IPMN in animal model and highlighted the role of Wnt/β-catenin pathway in KRAS-associated lesions [73].…”
Section: Genetics and Molecular Pathwaysmentioning
confidence: 94%